PERAN GURU DALAM MEMBENTUK EMOSIONAL TERHADAP PRESTASI BELAJAR SISWA SEKOLAH DASAR - Dela Rachmayana; Desyani Islamiyati; Endah Puspita Ningtyas; Rahmawati Eka Saputri (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
This study aims to reveal the role of teachers in shaping students' emotional aspects and its impact on academic achievement at the elementary school level. Using a descriptive qualitative approach, data were collected through observation and interviews with four students and two teachers. The results showed that three out of four students (75%) felt more motivated to learn due to emotional support from their teachers, and all students (100%) reported feeling comfortable in the classroom when they had a positive emotional connection with the teacher. Furthermore, 75% of the students stated that their academic performance improved after developing an emotional bond with the teacher. On the other hand, all teachers (100%) acknowledged the importance of emotional relationships in the learning process, although one teacher (50%) experienced initial difficulties in understanding students' diverse personalities. These findings emphasize that a teacher's role goes beyond delivering academic content; it also includes serving as an emotional companion who influences students' motivation, comfort, and overall academic success.